Widely tunable direct bandgap of two-dimensional GeSe. (24th December 2020) - Zhang, Yu; Wang, Xin-Xin; Shi, Li-Jie
Abstract: Bulk GeSe is an indirect bandgap semiconductor. However, direct bandgap semiconductor of two-dimensional GeSe can be obtained by applying strain along armchair direction, and the direct bandgap can be tuned in a wide energy range from 0.86 eV to 0.00 eV by electric field. The bandgap modulation mechanism is studied in detail by first-principle calculations. The calculations of phonon spectra show that the crystal structure is relatively stable under the strain and electric field. Therefore, 2D GeSe is a promising material in frequency adjustable electronic and optical devices.